Apert Syndrome: A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : Apert syndrome is a rare autosomal dominant disorder characterized by craniosynostosis, facial dysmorphism and syndactyly of hands and feet. Eugene Apert in 1906 describe the syndrome acrocephalosyndactyly.Case Presentation : The reporting case was a 3 months old female baby presented with early fusion of all cranial bone, facial dimorphism like hypertelorism, cleft palate and syndactyly of both hands and feet. There was some bony defect also found in radioligy.Conclusion : It is a noncurable disease but treat with multidisciplinary approach can reduce the complication and prevention can be done by genetic counselling and antenatal ultrasonography.Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 60-63